(untitled) (Discourse of Law and Administration, 2019)
The concept of “social security” exists in most national legislation of European countries in terms of international legal instruments. Also the Polish legislator determining the constitutional framework for the protection of insurance states that the citizen has the right to “social security”. However, despite the widespread use of this concept, it has not been previously defined anywhere and not been given any clear content. In this article the author attempts to define the term based on the analysis of the provisions relating to the pension system. This is particularly important character in the jurisdictions in which the pension system is based on the principle of apportioning benefits, which must specify the relationship between fundamental rights and constitutional methods of achieving them.